UPAYA GURU PEMBIMBING DALAM MENGEMBANGKAN POTENSI PSIKIS PESERTA DIDIK DI SMP NEGERI 9 PADANG - Yunas, Rini Septiani; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
The problem this research is how would be effort a directship and teacher in developing psychology potency the pupil at Junior High School Negeri 9 Padang. These research its purpose about is description (1) Be effort a teacher and directship in developing intellectual and inteligency potency the pupil. (2) Be effort a teacher and directship in developing emotional and inteligency the pupil . This research form is descriptive research .The population these research are all of the pupil at Junior High School Negeri 9 by sum of 718 person and 88 sampling person .These research being usefullProportionate Stratified Random Samplingor stratified sampling that is get off the sample from the populationhave divided in stratified or strata . The resources data whole is mean in the research have offered initial from proving its data. These tool and equipment all of group data are usefull a questioner sheet. The data is examined by usefullpercently technic. Concomitan here research and resulting have been found like is footnote below . (1) Be effort directship and teacher in developing intellectual the pupil at Junior High School Negeri 9 Padang have proved into good category. (2) Be effort directship and teacher in developing emotional inteligency the pupil at Junior High School Negeri 9 Padang into good category. Base on find out this research to recommendation on : directship and teacher proved to improvement psycho potency all of the pupil at Junior High School Negeri 9 Padang with optimally.